Development of an aviation-style computerized checklist displayed on a tablet computer for improving handoff communication in the post-anesthesia care unit. - Jelacic, Srdjan; Togashi, Kei; Bussey, Logan; Nair, Bala G.; Wu, Tim; Boorman, Daniel J.; Bowdle, Andrew (Journal of Clinical Monitoring & Computing, 2021)
Critical patient care information is often omitted or misunderstood during handoffs, which can lead to inefficiencies, delays, and sometimes patient harm. We implemented an aviation-style post-anesthesia care unit (PACU) handoff checklist displayed on a tablet computer to improve PACU handoff communication. We developed an aviation-style computerized checklist system for use in procedural rooms and adapted it for tablet computers to facilitate the performance of PACU handoffs. We then compared the proportion of PACU handoff items communicated before and after the implementation of the PACU handoff checklist on a tablet computer. A trained observer recorded the proportion of PACU handoff information items communicated, any resistance during the performance of the checklist, the type of provider participating in the handoff, and the time required to perform the handoff. We also obtained these patient outcomes: PACU length of stay, respiratory events, post-operative nausea and vomiting, and pain. A total of 209 PACU handoffs were observed before and 210 after the implementation of the tablet-based PACU handoff checklist. The average proportion of PACU handoff items communicated increased from 49.3% (95% CI 47.7-51.0%) before checklist implementation to 72.0% (95% CI 69.2-74.9%) after checklist implementation (p < 0.001). A tablet-based aviation-style handoff checklist resulted in an increase in PACU handoff items communicated, but did not have an effect on patient outcomes.